Living up to your own standards?: Patterns of civic norms and volunteering in Germany - Ackermann, Kathrin; Mylius, Jonathan; Haußmann, Annette; Wiloth, Stefanie (Social Inclusion, 2025)
Kathrin Ackermann, Jonathan Mylius, Annette Haussmann, Stefanie Wiloth